The politics of the unknown: Uncertainty and the nuclear threat in Britain, 1979–1985. Issue 12 (29th October 2018) - Laucht, Christoph
Abstract: This article seeks to map out possibilities for conducting a microhistorical study of the socio‐political and cultural roles that uncertainty, as a consequence of a lack of verifiable knowledge, played in political debates over the nuclear threat in Britain in the Second Cold War. Focusing on this politics of the unknown in the period from 1979 to 1985 when Britain witnessed resurging fears of nuclear war, this exploratory essay sets out to make three main interventions: First, it conceptualizes "uncertainty" as a subjective social and cultural construct with fluid meanings that does not necessarily have to hold exclusively negative connotations but might offer opportunities for historical actors. Second, this essay proposes an examination of the politics of the unknown about the anticipated effects of a nuclear war within a wider synchronic economy of non‐nuclear‐weapons‐related concerns such as de‐industrialization or unemployment. Finally, the article introduces the periodization of "Britain's long nuclear 1980s" to allow for a consideration of relevant diachronic aspects of this politics of the unknown, thereby adding further depth to the microhistory. Throughout, this exploratory study draws on historical examples to illustrate its key theoretical points.